A Community of Many Worlds: Arab Americans in New York City by Kathleen Benson and Philip M. Kayal, eds. (New York: The Museum of the City of New York, 2002. 280 pages.) (American Journal of Islam and Society, 2005)
This edited collection complemented a March 2001 museum exhibit and isbased upon a February 2000 Columbia University conference and a threeyearFord Foundation-sponsored research project. It provides a generaloverview of the history and diversity of Arab Americans in New York Cityand is particularly strong in the area of the arts, featuring several chapters onliterature and music, including several first-person narratives. This two-partbook, which surveys both the historical and the contemporary scenes, isfurther enhanced by forty black-and-white photographs, including thirteenby Empire State College’s Mel Rosenthal.New York contains the third largest Arab-American community, afterDearborn (Michigan) and Los Angeles. In the first chapter, Alixa Naffexplains that the community was formed around 1895, when Christian missionaries in Syria encouraged Arab Christians near Mount Lebanon to workin New York for a couple of years to make money for their families. Syrianand Lebanese immigrants initially gathered at Washington Street in LowerManhattan and soon moved to Atlantic Avenue in the South Ferry portion ofBrooklyn. From 1899-1910, 56,909 Syrian immigrants arrived in New York.In the book’s first part, two historical chapters are followed by entrieson literature, music, photography, and first-person accounts. Philip Kayalpoints out that Arab-American is a cultural and ethnic – but not a religious– category, for most Arab Americans are Christian, not Muslim. JonathanFriedlander reveals that the first Arab-American immigrant, AntonioBishallany, visited from Lebanon in 1854 to gather evangelical teachings foruse back home. This four-page and six-photograph entry on representationsin historical archives could be expanded into a larger work ...